Temperature distributions in boreholes of a vertical ground-coupled heat pump system - Esen, Hikmet; Inalli, Mustafa; Esen, Yuksel (Pergamon-Elsevier Science Ltd, 2009)
The objective of this study is to show the temperature distribution development in the borehole of the ground-coupled heat pump systems (GCHPs) with time. The time interval for the study is 48 h. The vertical GCHP system using R-22 as refrigerant has a three single U-tube ground heat exchanger (GHE) made of polyethylene pipe with a 40 mm outside diameter. The GHE was placed in a vertical borehole (VB) with 30 (VB1). 60 (VB2) and 90 (VB3) m depths and 150 mm diameters. The experimental results were obtained in cooling and heating seasons of 2006-2007. A two-dimensional finite element model (FEM) was developed to simulate temperature distribution development in the soil surrounding the GHEs of GCHPs operating in the cooling and the heating modes. The finite element modelling of the GCHP system was performed using the ANSYS code. The FEM incorporated pipes, the grout and the surrounding formation. From the cases studied, this approach appears to be the most promising for estimation the temperature distribution response of GHEs to thermal loading. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Ground heat exchanger; Heat pump; Heating; Cooling; Finite element; Borehole